The Role of E-Word of Mouth in the Relationship between Online Destination Image, E-satisfaction, E-Trust & E-Service Quality for International Tourists Perception - Faisal A. al-Bourini; Nader Mohammad Aljawarneh; Mohammad Fathi Almaaitah; Shadi Altahat; Ziyad Saleh Alomari; Munsif Sokiyna (Journal of Information Technology Management)
Destination Image as a development which comprises of interrelated assessments converged with general impressions and convictions dependent on data preparing from an assortment of sources after some time; little research has concentrated on picture arrangement corresponding to this kind of goal, this article explores the mediating role of Online Image on the connection between E-WOM and  E-service quality, E-satisfaction, E- trust The result of Structural equation Modelling  (AMOS) path analysis affirmed that estimation model fulfilled the necessity and evidence the solidness of things, builds and correlation. All the four conditions for estimation model was met: things stacking above 0.7; unwavering composite quality (CR) above 0.7; Average Variance Extraction (AVE) above 0.5. The scholastics and industry will profit by the usage of this examination. Likewise, the tourist industry division can draw from these outcomes as references and proposals inside the impediments of the study. Future research headings were proposed to deal with the restrictions.